# Question: Show how the derivation of the binomial probabilities leads to a

Show how the derivation of the binomial probabilities

leads to a proof of the binomial theorem

when x and y are nonnegative.

Let p = x / x + y.

leads to a proof of the binomial theorem

when x and y are nonnegative.

Let p = x / x + y.

## Answer to relevant Questions

Let X be a random variable with probability density function (a) What is the value of c? (b) What is the cumulative distribution function of X? The annual rainfall (in inches) in a certain region is normally distributed with μ = 40 and σ = 4. What is the probability that, starting with this year, it will take over 10 years before a year occurs having a rainfall of ...The lifetimes of interactive computer chips produced by a certain semiconductor manufacturer are normally distributed with parameters μ = 1.4 × 106 hours and σ = 3 × 105 hours. What is the approximate probability that a ...Suppose that the life distribution of an item has the hazard rate function λ(t) = t3, t > 0. What is the probability that (a) The item survives to age 2? (b) The item’s lifetime is between .4 and 1.4? (c) A 1-year-old ...Let f(x) denote the probability density function of a normal random variable with mean μ and variance σ2. Show that μ − σ and μ + σ are points of inflection of this function. That is, show that f″(x) = 0 when x = ...Post your question